The Impact of Norms Generality on MAS Goal - Alves, Jhonatan; Hübner, Jomi Fred; Marchi, Jerusa (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC), 2021)
In this paper we aim to investigate the impact of levels of generality on norms synthesized on the global goal satisfiability and conflicts avoidance of Normative Multiagent Systems. We found out that exists a level of generality in the scenarios we perform some experiments, which we call apex level, where norms tend to be efficient in avoiding conflicts while ensuring goal system reachability.